2015
DOI: 10.1017/s0022149x15000954
|View full text |Cite
|
Sign up to set email alerts
|

Infection levels and seasonality of monogeneans in the largemouth bassMicropterus salmoides(Perciformes: Centrarchidae) from Nuevo León, Mexico

Abstract: Largemouth bass, Micropterus salmoides, is a native fish species with special importance for sport fishing competitions in Nuevo León, Mexico. However, no study has investigated the parasitic fauna of M. salmoides, and no reports are available on monogenean parasites in this fish species. Therefore, we described the monogenean parasites of M. salmoides and the effects of season and fish condition factor in five reservoirs: La Boca (LB), El Cuchillo-Solidaridad (CS), Sombreretillo (S), Laguna Salinillas (LS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The species O. principalis has a high level of specificity to the genus Micropterus, what makes it presence an event of co-introduction (Maitland & Price, 1969;Margolis & Kabata, 1984;Collins & Janovy, 2003). Although, over the several monogenean species that parasite M. salmoides (Hoffman, 1999;Galaviz-Silva et al, 2016;Costa et al, 2018), only one was found in this study. This shows a clear example of enemy release, still the high abundance of O. principalis in two of the reservoirs sampled could be a compensation of the poor parasite richness (Colautti et al, 2004;Roche et al, 2010).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The species O. principalis has a high level of specificity to the genus Micropterus, what makes it presence an event of co-introduction (Maitland & Price, 1969;Margolis & Kabata, 1984;Collins & Janovy, 2003). Although, over the several monogenean species that parasite M. salmoides (Hoffman, 1999;Galaviz-Silva et al, 2016;Costa et al, 2018), only one was found in this study. This shows a clear example of enemy release, still the high abundance of O. principalis in two of the reservoirs sampled could be a compensation of the poor parasite richness (Colautti et al, 2004;Roche et al, 2010).…”
Section: Resultsmentioning
confidence: 60%
“…(Hoffman, 1999;Tavakol et al, 2015). The same is true for the monogenean O. principalis (Galaviz-Silva et al, 2016). However, the nematode P. peraccuratus is a parasite native to South America, which makes its infection in M. salmoides a possible instance of parasite spillback (Azevedo et al, 2006;Takemoto et al, 2009).…”
Section: Resultsmentioning
confidence: 99%